Molecular Testing for Diagnostics, Prognostication, and Treatment Stratification in Cancers. Issue 1 (January 2023) - Heneidi, Saleh; Golden, Jeffrey A.; Vail, Eric
Abstract: Precision cancer care, for essentially all cancer types, now requires molecular diagnostics to assess mutations, chromosomal alterations, and gene expression to personalize treatments for individual patients. Advances in the diagnostics and treatment options have moved the field forward from fundamental discoveries beginning in the 1960s to the development of many targeted therapies that can be as specific as targeting a single-base-pair mutation. Herein is a brief historical perspective on cancer precision medicine with current diagnostic, prognostic, and treatment stratification guidance for early- and late-stage cancers.